Using Gordiid cysts to discover the hidden diversity, potential distribution, and new species of Gordiids (Phylum Nematomorpha) - Harkins, Cleo; Shannon, Ryan; Papeş, Monica; Schmidt-Rhaesa, Andreas; Hanelt, Ben; Bolek, Matthew G. (Zootaxa, 2016)
In this study, we sampled aquatic snails for the presence of hairworm cysts from 46 streams in Payne County, Oklahoma. Gordiid cysts were found at 70 % (32/46) of sites examined. Based on cyst morphology, we were able to identify three morphological types of gordiid cysts, including Paragordius, Gordius, and Chordodes/Neochordodes. Using our gordiid cyst presence data in conjunction with environmental variables, we developed an ecological niche model using Maxent to identify areas suitable for snail infections with gordiids. The model successfully predicted all presence localities of gordiid cysts in snails over a geographic area of 1,810 km2. We used this information, along with arthropod host infections and crowdsourcing, citizen scientists sampling for adult free-living worms during peak emergent times in areas predicted suitable by the model, to document Paragordius varius, Chordodes morgani, and a new species of gordiid (Gordius n. sp.). To our knowledge, this is the first ecological niche model attempted on such a narrow geographic scale (county level) that recovered known locations successfully. We provide new scanning electron micrographs and molecular data for these species. Our field data and ecological niche model clearly indicate that gordiid cysts are easy to detect in the environment and together these sampling techniques can be useful in discovering new species of gordiids, even in relatively well sampled areas for these cryptic parasites.